2017
DOI: 10.5194/isprs-annals-iv-2-w4-185-2017
|View full text |Cite
|
Sign up to set email alerts
|

Automated Coarse Registration of Point Clouds in 3d Urban Scenes Using Voxel Based Plane Constraint

Abstract: ABSTRACT:For obtaining a full coverage of 3D scans in a large-scale urban area, the registration between point clouds acquired via terrestrial laser scanning (TLS) is normally mandatory. However, due to the complex urban environment, the automatic registration of different scans is still a challenging problem. In this work, we propose an automatic marker free method for fast and coarse registration between point clouds using the geometric constrains of planar patches under a voxel structure. Our proposed metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 29 publications
1
31
0
2
Order By: Relevance
“…In order to improve performance by reducing processing time, calculations were performed on the entire series simultaneously instead of through looping over arrays. The use of voxels, a higher-level geometric structure, is more robust and flexible than a single key point or feature lines because voxels have fewer geometric constraints [17]. Assuming original observations are accurate, the algorithm groups 3D point cloud data within non-overlapping fishnets into voxels.…”
Section: Voxelizationmentioning
confidence: 99%
“…In order to improve performance by reducing processing time, calculations were performed on the entire series simultaneously instead of through looping over arrays. The use of voxels, a higher-level geometric structure, is more robust and flexible than a single key point or feature lines because voxels have fewer geometric constraints [17]. Assuming original observations are accurate, the algorithm groups 3D point cloud data within non-overlapping fishnets into voxels.…”
Section: Voxelizationmentioning
confidence: 99%
“…Considering that in the same scene, the basic geometric structures of the buildings are always consistent (Boerner et al, 2018), we developed the strategy of using geometric primitives to align these two coordinate frames. Here, the primitives we used include lines (Koch et al, 2016) and planes (Xu et al, 2017a) The ways of extracting 3D lines have been widely reported. For example, the 3D lines can be reconstructed from a set of images using the method of (Hofer et al, 2017) or (Jain et al, 2010).…”
Section: Primitive Extractionmentioning
confidence: 99%
“…While for extracting 3D lines from LiDAR point clouds, methods are reported in (Lin et al, 2017) or (Hackel et al, 2016), aim at extracting boundaries and contours of the point cloud. As for the extraction of planes, there are also plenty of work like (Xu et al, 2017a, Nguyen et al, 2017, Dong et al, 2018. The benefits of using 3D lines and planes lie on less heavy computational cost than points, because such primitives always represent important structures of the environment for finding correspondences (esp.…”
Section: Primitive Extractionmentioning
confidence: 99%
See 2 more Smart Citations